Interobserver Agreement in Magnetic Resonance Imaging of Active Sacroiliitis - Emel Gönüllü; Yasemin Gündüz; Ünal Erkorkmaz; Aysel Toçoğlu; Damla Karataş; Zeynep Öztürk; Fevziye Türkoğlu Genç; Ahmet Burak Kara; Ahmed Cihad Genç (Sakarya Tıp Dergisi, 2023)
Introduction Axial spondyloarthritis has characteristic clinical features such as enthesitis, sacroiliitis and spondylitis, and extra-articular manifestations. Sacroiliitis (SI) occurs as a result of inflammation of the sacroiliac joint. Magnetic resonance imaging (MRI) of sacroiliac (SI) joints is used to detect early sacroiliitis. Sometimes, there can be variations in the interpretation of MRI findings of the SI joint among observers. Our aim was to investigate the inter-observer agreement among the observers. Materials and methods The study included the MRI results of 1150 patients who were diagnosed with active or chronic sacroiliitis based on the findings from sacroiliac MRIs, or whose MRI was deemed indicative of sacroiliitis by the rheumatologist. 1150 MRIs were re-evaluated by a different and expert radiologist. Results Out of the total 1150 patients investigated within the scope of this study. A statistically significant disparity emerged between the assessments provided by the expert radiologists and those obtained from outsourced radiologist evaluations. Conclusion The diagnosis of spondyloarthropathy may be delayed for some reasons. If the patient's clinic and MRI report are not consistent, the patient should not be removed from follow-up.